A review on the avoidance and evasion of income tax by urban unorganized sector of Punjab, India - Sharma, Kirti; Arora, Jyoti (Gyan Management Journal, 2022)
Taxes are major source of revenue to the government. Tax evasion and avoidance are pervasive in all countries and which hampers the economic development to greater extent. The present research brings out the issue that integrate avoidance and evasion by the urban unorganised sector of Punjab state which consist of workers or professionals who neither have registration number nor monitored by government directly. To meet the objective, the require data it is collected from primary as well as secondary sources which are collected from 50 respondent which cover the aspect relevant to income factor, total revenue, tax payment or non-payment related to prescribed sector. This review paper focuses on highlighting the cause and ill effect of tax evasion by unorganised sector which hinders the overall development of state and country and finding the relevant measure which the tax administration authorities can strategically and efficiently apply to combat with the tax evasion in income tax by the unorganised sector.